(untitled) (REC 2026 - 11th International Workshop on Reliable Engineering Computing: Reliability Computations in a Data and Model-Driven World, 2026)
A key issue for the determination of the mechanical properties of heterogeneous materials is the existence of a broad range of length scales that govern their behavior. This work presents an effective multiscale computational framework for modeling the spatially varying mechanical properties of heterogeneous materials using random fields derived directly from microstructure images through homogenization combined with the moving window technique. Two applications are provided to illustrate the proposed computational framework. The determination of random fields of bending stiffness properties based on real CT-image data of short fiber composites and the computation of the apparent elasticity tensor of additively manufactured structures with random microstructural defects. The random field models of the first application can be employed for the response variability analysis of composite plates using Monte Carlo simulation. Useful conclusions are derived regarding the effect of scale factor, inter- and intra-layer overlap of printed filament lines on the mesoscale random fields.